Don't be Afraid, Little Foal - Pitcher, Caroline (Magi Publications, 1998)
Little Foal is afraid to be alone, and he doesn't ever want to be without his mother who takes care of him. But one day he wakes up to find his mother is going for a ride and he must stay behind. How will he manage without her?
Keywords: Juvenile literature-Fiction